ANALYSIS OF BANKS ACTIVITIES THAT HAVE SUCCESSFULLY IMPLEMENTED DIGITAL INNOVATIONS IN UZBEKISTAN - Gulbakhor Matyakubovna Bakoeva (American Journals, 2024)
The article focuses on analysis of banks activities that have successfully implemented digital innovations in Uzbekistan. The main tendencies and measures, concerned to digitalization of banking and financial operations were researched.
Keywords: Digitalization, emission, bank transactions, financial services, fintech, bank capitalization.